2007
DOI: 10.1017/s1751731107736741
|View full text |Cite
|
Sign up to set email alerts
|

Synchronising the availability of amino acids and glucose increases protein retention in pigs

Abstract: Effects of synchronising the availability of amino acids and glucose within a day on protein and energy metabolism were studied in growing pigs. Ten pigs of on average 54 (s.e. 1.0) kg live weight were assigned to each of two dietary treatments (synchronous v. asynchronous nutrient supply) in a change-over design. On the synchronous treatment (SYN), pigs received two balanced meals: one at 0800 h and one at 1600 h. On the asynchronous treatment (ASYN), pigs received virtually all protein at 0800 h and all carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Irrespective of castration method, AHP accounted for 8.6% of ME intake, which agrees with previous observations in growing pigs fed close to ad-libitum (from 7.6 to 11.6% of ME intake; Schrama et al, 1998; Le Bellego et al, 2001; Quiniou et al, 2001; van den Borne et al, 2007; Labussière et al, 2011; Renaudeau et al, 2013) but values were highly variable between animals (Figure 3). To account for the possible bias induced by the variation in AHP between animals, a calculation routine was used to standardize AHP between animals, which resulted in variations in TEF c and RE c .…”
Section: Discussionsupporting
confidence: 90%
“…Irrespective of castration method, AHP accounted for 8.6% of ME intake, which agrees with previous observations in growing pigs fed close to ad-libitum (from 7.6 to 11.6% of ME intake; Schrama et al, 1998; Le Bellego et al, 2001; Quiniou et al, 2001; van den Borne et al, 2007; Labussière et al, 2011; Renaudeau et al, 2013) but values were highly variable between animals (Figure 3). To account for the possible bias induced by the variation in AHP between animals, a calculation routine was used to standardize AHP between animals, which resulted in variations in TEF c and RE c .…”
Section: Discussionsupporting
confidence: 90%
“…In his study, better FCR was observed with KDS values closer to 1.26 h −1 , whereas in the present report, a KDS value of 1.80 h −1 impaired performance. According to Van den Borne et al (2007), pig performance is maximized when the absorption of energy-providing nutrients and amino acids for protein synthesis is synchronized. Black et al (2005) proposed an asynchrony in the timing of absorption of amino acids and glucose as an explanation to the lower energy utilization from sorghum than from wheat-based diets in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…In single-stomach animals, variations in the rate of starch digestion have several implications on digestion and absorption of nutrients, and on animal performances [23][24]. An asynchronous availability of nutrients (glucose and amino-acids) within a day could negatively affect protein utilization by consumers [25]. These kinds of information are not provided when only glucose is measured after digestion.…”
Section: Effect Of Post-incubation With Amyloglucosidase On Carbohydrmentioning
confidence: 99%